THE NATIONAL INTEREST CONCEPT IN A GLOBALISED INTERNATIONAL SYSTEM - Rifki Dermawan (Indonesian Association for International Relations, 2019)
Globalisation creates changes at the national level and also in the international system. The concept of state along with its national interest are challenged by globalisation process. As a significant part of foreign policy, the national interest concept needs an adjustment in this modern era. The emergence of non-state actors also contribute to the transformation of global community. The large number of states integrate in international or regional organisations cause a tension between national interest and collective interest of a state. Therefore, this article suggests that a state needs to reconsider its concept of national interest since there are many changes occur in the globalised international system. The “old ideas of national interest” proposed by realists could be irrelevant in the today’s world.